2005
DOI: 10.1071/ar05006
|View full text |Cite
|
Sign up to set email alerts
|

The importance of accounting for maternal genetic effects in Australian fine-wool Merino breeding

Abstract: (Co) variances for greasy fleece weight (GFW), clean fleece weight (CFW), mean fibre diameter (MFD), staple strength (SS), coefficient of variation of fibre diameter (CVFD), birthweight (BW), weaning weight (WW), and yearling weight (YW) were estimated for 5108 Australian Merino sheep from the CSIRO Fine Wool Project, born between 1990 and 1994. Covariances between these traits and number of lambs weaned per ewe joined (NLW) were also estimated. Significant maternal genetic effects were found for GFW, CFW, BW,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
10
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 4 publications
9
10
6
Order By: Relevance
“…Maternal correlations were 0.84 between LW and GFW, 0.46 between LW and CFW, 0.85 between fleece weights, 0.08 between GFW and FD and 0.19 between CFW and FD. The maternal correlation was accordingly high (0.98) between GFW and CFW in Australian Merinos (Asadi Fozi et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Maternal correlations were 0.84 between LW and GFW, 0.46 between LW and CFW, 0.85 between fleece weights, 0.08 between GFW and FD and 0.19 between CFW and FD. The maternal correlation was accordingly high (0.98) between GFW and CFW in Australian Merinos (Asadi Fozi et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Several studies reported significant maternal effects for LW, GFW and CFW for various sheep breeds (Asadi Fozi et al, 2005;Cloete et al, 2005;Safari et al, 2005). In contrast, Vaez Torshizi et al (1996) reported no significant maternal effects for any of the corresponding objective wool traits beyond 12 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there appears to be a strong negative correlation between direct and maternal genetic effects for fleece weight, this correlation is closer to zero for bodyweight. Asadi Fozi et al (2005) showed that accounting for maternal genetic effects in Merino breeding objectives led to more 0.68 ± 0.09 0.60 ± 0.13 0.58 ± 0.12 0.54 ± 0.08 0.09 ± 0.02…”
Section: Maternal Effectsmentioning
confidence: 99%
“…In addition, preliminary estimates of heritabilities and correlations from subsets of the complete dataset of the Fine Wool Project flock have been published by Swan et al (1995), Purvis and Swan (1997) and Asadi Fozi et al (2005). While collectively these studies have shown that fine wool genetic parameters are not substantially different to medium wool parameters, the complete Fine Wool Project dataset now provides us with the ability to investigate this issue with greater precision.…”
Section: Introductionmentioning
confidence: 99%